Cardioprotective shock management: monitoring and supportive therapies. (27th March 2021) - Schibilsky, David; Delmas, Clement; Bonello, Laurent; Hunziker, Patrick
Abstract: Cardiogenic shock is a highly lethal syndrome, leading to rapid death or secondary multiorgan damage, but current shock therapies, including mechanical support devices, also have a significant side effect profile. The overarching goal of shock therapy is ensuring long-term survival with good quality of life. This implies averting death, modifying the disease course by promoting heart recovery and avoiding additional cardiac damage, protecting other organs, and circumventing complications. Monitoring and supportive therapies are subordinate to these goals. Rather than merely following preconceived notions, the rapid evolution in mechanical support technology requires iterative and critical review of the benefits of current procedures, protocols and drugs in view of their overall contribution to the therapeutic goals. This article discusses various monitoring and supportive pharmaceutical modalities typically used in patients with cardiogenic shock requiring mechanical support.